Syariah Card Mechanism in The Capitalism Infrastructure - Ulinnuha Saifullah; Khairul Imam; Setiyawan Gunardi (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2026)
Normative reconstruction of credit card mechanisms under sharia principles raises a central question about whether contractual compliance also changes economic substance. Focusing on Syariah Card (a sharia-based credit card arrangement), this article examines Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (National Sharia Board legal opinion) No. 54/DSN-MUI/X/2006, Bank Indonesia payment-system regulations, fee structures, and relevant Islamic finance literature through normative-comparative legal analysis. The analysis shows that Syariah Card differs normatively from conventional credit cards through kafālah, qarḍ, ijārah, ujrah, taʿwīḍ, taʿzīr, the prohibition of ribā, restrictions on non-Islamic transactions, and the prevention of isrāf. These differences are legally significant and should not be reduced to mere terminology. However, Syariah Card remains embedded in modern payment capitalist infrastructure involving issuers, merchants, acquirers, billing cycles, settlement, merchant fee, and transaction-based income. Merchant fee or MDR becomes the critical point because it links issuer income to transaction volume without being identical to interest. Therefore, maqāṣid al-sharīʿah must evaluate not only contractual validity, but also fee transparency, consumer protection, prevention of excessive consumption, and ḥifẓ al-māl. Rekonstruksi syariah atas mekanisme kartu kredit menimbulkan pertanyaan penting mengenai apakah kepatuhan akad juga mengubah substansi ekonominya. Artikel ini mengkaji Syariah Card melalui Fatwa DSN-MUI No. 54/DSN-MUI/X/2006, regulasi sistem pembayaran Bank Indonesia, struktur biaya, dan literatur keuangan syariah dengan pendekatan hukum normatif-komparatif antara Syariah Card dengan kartu kredit konvensional. Hasil kajian menunjukkan bahwa Syariah Card memiliki perbedaan normatif dari kartu kredit konvensional melalui akad kafālah, qarḍ, ijārah, ujrah, taʿwīḍ, taʿzīr, larangan ribā, larangan transaksi non-syariah, serta pencegahan isrāf. Perbedaan ini memiliki arti hukum yang nyata dan tidak dapat direduksi sebagai penggantian istilah semata. Namun, Syariah Card tetap bekerja dalam infrastruktur kapitalisme dengan mekanisme pembayaran modern yang melibatkan penerbit, pedagang, acquirer, siklus tagihan, settlement, merchant fee, dan pendapatan berbasis transaksi. Merchant fee atau MDR menjadi titik kritis karena menghubungkan pendapatan penerbit dengan volume transaksi, meskipun tidak identik dengan bunga. Karena itu, maqāṣid asy-syarīʿah perlu digunakan untuk menilai transparansi biaya, perlindungan konsumen, pencegahan konsumsi berlebihan, dan ḥifẓ al-māl (penjagaan terhadap harta).